Pengaruh Model Pembelajaran Somatic, Auditory, Visualization, Intellectually (SAVI) Berbantuan Media Ask Puzzle terhadap Kemampuan Berpikir Kritis Siswa Kelas IV SD Isriati Moenadi - Maya Mustafidah; Kartika Yuni Purwanti (Jurnal Sekolah Dasar, 2023)
This study aims to determine the effect of the Somatic, Auditory, Visualization, Intellectually (SAVI) learning model assisted by the ask puzzle on students’ critical thinking skills. The type of research used is quantitative research using experimental methods in the form of non-equivalent control group design. The population in this study was the fourth grade students of SD Isriati Moenadi, with a sample of grade IV A students as the experimental class and class IV B students as the control class. Data collection techniques used are tests, observations, questionnaires, and documentation. Data were analyzed by normality test, homogeneity test, independent sample t-test, and regression test. The results showed : 1) There were differences from the use of the SAVI learning model assisted by ask puzzle on students’ critical thinking skills, as evidenced by the results of the independent sample t-test which showed that the average of the experimental class was hinger than the control class, namely 77,8 > 73,8 and with a significance value of 0,012 < 0,05. 2) There is an influence from the use of the SAVI learning model assisted by the ask puzzle on students’ critical thinking skills, as evidenced by the results of the regression test showing a significance of 0,00 < 0,05 which means that X has an effect on Y and the value of R square or R2 = 0,799 = 79% (X affects Y by 79%). So it can be concluded that the SAVI learning model assisted by the media ask puzzle has an effect on the critical thinking skills of fourth grade student at SD Isriati Moenadi.